2016
DOI: 10.1146/annurev-earth-060115-012348
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Brachiopoda

Abstract: Brachiopods are (perhaps all too) familiar to any geology student who has taken an invertebrate paleontology course; they may well be less familiar to biology students. Even though brachiopods are among the most significant components of the marine fossil record by virtue of their considerable diversity, abundance, and long evolutionary history, fewer than 500 species are extant. Reconciling the geological and biological perspectives is necessary in order to test hypotheses, not only about phylogenetic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 133 publications
4
92
0
3
Order By: Relevance
“…This information is systematised so well that it makes this book a prime source of general knowledge of this group. The importance of this source is comparable to that of a review just published by Carlson (2016). Of course, knowledge gathered in the first part of the present book also facilitates understanding the second portion.…”
supporting
confidence: 54%
“…This information is systematised so well that it makes this book a prime source of general knowledge of this group. The importance of this source is comparable to that of a review just published by Carlson (2016). Of course, knowledge gathered in the first part of the present book also facilitates understanding the second portion.…”
supporting
confidence: 54%
“…However, globally, the earliest Iberian radiation can be correlated with the recovery of linguliformean faunas on all major Early Palaeozoic platforms during the mid-Tremadocian (P. deltifer conodont Zone)-mid-Floian (Oepikodus evae conodont Zone) interval (Harper et al 2004). According to Carlson (2016), this recovery mostly occurred within the Lingulida, Acrotretida and the Siphonotretida. The current study has only found taxa assigned to the Lingulida in Iberia at this time.…”
Section: Temporal Development Of Diversity Pulsesmentioning
confidence: 99%
“…), thus providing an advantage over most articulated brachiopods, which had calcareous shells and went extinct; and (2) Orbiculoidea developed an advanced feeding system according to Williams et al . (), both Discina and Discinisca (within the Family Discinidae Gray, ) possess a spirolophous lophophore, which is one of the most developed types in brachiopods (Carlson ). Thus, Orbiculoidea also probably had a spirolophous lophophore to help to generate inhalant and exhalant flows of water, trap particulate food material and remove waster products, which would have enhanced its chance of survival in the nutrient‐poor oceans.…”
Section: Discussionmentioning
confidence: 99%